Fusion imaging techniques and contrast-enhanced ultrasound for thermal ablation of hepatocellular carcinoma – A prospective randomized controlled trial. (1st January 2019) - Huang, Qiannan; Zeng, Qingjing; Long, Yinglin; Tan, Lei; Zheng, Rongqin; Xu, Erjiao; Li, Kai
Abstract: Objectives: This randomized controlled trial (RCT) aims to compare the clinical application values of contrast-enhanced ultrasound (CEUS), computed tomography/magnetic resonance-CEUS (CT/MR-CEUS), and three-dimensional ultrasound-CEUS (3DUS-CEUS) Fusion imaging (FI) techniques in the assistance of thermal ablation for hepatocellular carcinoma (HCC). Methods: A RCT was conducted on 374 patients with 456 HCCs between January 2016 and September 2017. CEUS, CT/MR-CEUS, and 3DUS-CEUS FI techniques were randomly used to assist HCC ablation. All lesions were ablated according to a previously determined plan, and FI groups required a 5-mm ablative margin. The primary endpoints were technical efficacy of thermal ablation and local tumor progression (LTP). Results: According to randomization, 153 (18.8 ± 8.0 cm), 153 (18.3 ± 6.6 cm) and 150 (19.1 ± 6.9 cm) HCCs were assigned to CT/MR-CEUS, 3DUS-CEUS and CEUS groups respectively. Technical efficacy rates (99.3% vs. 100% vs. 100%) were achieved in the three groups, showing no statistical differences ( p = 1.000). The median follow-up time was 24 (1–37) months. LTP rates at 1 and 2 years were 3.4%, 12.2% for CT/MR-CEUS FI, 4.8%, 9.0% for 3DUS-CEUS FI, and 8.6%, 19.9% for CEUS, respectively ( p = .105). The results of subgroup analysis for LTP were statistically significant when patients with albumin-bilirubin (ALBI) grade 2 and 3 ( p = .000), and tumor located at risky positions ( p = .042). In addition, the p value in group of multiple tumors was close to .05 ( p = .052). Conclusions: All the three techniques are feasible for intraoperative HCC thermal ablation. Compared with CEUS, FI techniques are more suitable in patients with ALBI grade 2 and 3, multiple tumors, and in tumors at risky locations.